Association of maternal thyroid peroxidase antibody during pregnancy with placental morphology and inflammatory and oxidative stress responses - Ru, Xue; Yang, Mengting; Teng, Yuzhu; Han, Yan; Hu, Yabin; Wang, Jianqing; Tao, Fangbiao; Huang, Kun (Frontiers in Endocrinology, 2023)
Background Studies suggest that thyroid peroxidase antibody (TPOAb) positivity exposure during pregnancy may contribute to changes in placental morphology and pathophysiology. However, little is known about the association of maternal TPOAb during pregnancy with placental morphology and cytokines. This study focuses on the effect of repeated measurements of maternal TPOAb during pregnancy on the placental morphology and cytokines. Methods Based on Ma’anshan Birth Cohort (MABC) in China, maternal TPOAb levels were retrospectively detected in the first, second and third trimesters. Placental tissues were collected 30 minutes after childbirth, placental morphological indicators were obtained by immediate measurement and formula calculation, and cytokine mRNA expression was detected by real-time quantitative polymerase chain reaction (RT-qPCR) afterward. Generalized linear models and linear mixed models were analyzed for the relationships of maternal TPOAb in the first, second and third trimesters with placental indicators. Results Totally 2274 maternal-fetal pairs were included in the analysis of maternal TPOAb levels and placental morphology, and 2122 pairs were included in that of maternal TPOAb levels and placental cytokines. Maternal TPOAb levels in early pregnancy were negatively associated with placental length, thickness, volume, weight and disc eccentricity, while positively correlated with placental IL-6, TNF-α, CRP, CD68, MCP-1, IL-10, HO-1, HIF-1α and GRP78. In mid-pregnancy, maternal TPOAb levels were negatively correlated with placental length, width and area. In late pregnancy, maternal TPOAb levels were negatively correlated with placental length, area, volume and weight. Repeated measures analysis showed that maternal TPOAb positivity tended to increase placental TNF-α, CD68 and MCP-1 while decreasing placental length, width and area than TPOAb negativity. Repeated measures analysis showed that maternal TPOAb levels were positively correlated with placental IL-6, TNF-α, CD68, MCP-1, IL-10, HO-1, HIF-1α and GRP78, while negatively correlated with placental length, area, volume, weight, and disc eccentricity. Conclusion There may be trimester-specific associations between maternal TPOAb levels and placental morphology and inflammatory and oxidative stress responses. The effect of maternal TPOAb levels on placental morphology is present throughout pregnancy. Early pregnancy may be the critical period for the association between maternal TPOAb levels and placental inflammatory and oxidative stress responses.